Competing Regionalisms in the Asia-Pacific? Versatile Sustainable Development Issues in FTAs - Kettunen Erja (Taylor & Francis, 2025)
The essay explores the inclusion of sustainability commitments in free trade agreements (FTAs) in the Asia-Pacific and the potential differences in their emphases that may reflect “competing regionalisms” in the region. Discussing the geo-economics of cross-border regionalism, the diverse trade agreements are compared as to provisions on sustainable development, and reflected with European Union FTAs. Findings indicate a lack of sustainable development issues in the Regional Comprehensive Economic Partnership and in China’s FTAs with regional neighbors, whereas the Trans-Pacific Partnership, and its successor, the Comprehensive and Progressive Agreement for Trans-Pacific Partnership, have substantial commitments on environmental and labor protection. The results suggest that the role of advanced economies as norm setters in sustainability policies may be challenged by a shift toward other emphases in Asia-Pacific FTAs. This contributes to our understanding of the cross-currents in global trade regime leading to competing regionalisms, and therefore, the limits to multilateralizing sustainability issues.